Effects of different levels of expanded perlite on the performance and egg quality traits of laying hens - Fatma Karakas Oguz; Hidir Gumus; Mustafa Numan Oguz; Kadir Emre Bugdayci; Hüseyin Dagli; Yasin Ozturk (Revista Brasileira de Zootecnia)
ABSTRACT The influence of different levels of expanded perlite on the performance and egg quality traits was studied in laying hens. Forty Lohmann Brown females at 30 weeks of age were randomly assigned to four groups consisting of five replicates with two hens in each. Four diet groups were supplemented with 0% (control group), 1%, 2%, and 3% perlite, respectively. Feed and water were provided ad libitum. There were no significant differences in final body weight, feed intake, egg yield, and egg weight. Feed conversion ratio and egg weight decreased with addition of 2% perlite. Dietary perlite supplementation has no significant effects on shape, yolk, and albumen index. Haugh unit was affected significantly by addition of 2% perlite. Fecal pH, dry matter, and NH3-N did not significantly differ among treatments. Dietary perlite has no negative effect on performance and egg quality traits except 2% perlite group. Dietary expanded perlite can be added at 1% level in laying hen rations without changing the animal performance.